Many Doors: The Histories and Philosophies of Roy Hart Voice Work and Estill Voice Training. Issue 2 (4th May 2019) - Caleo, Susan Bamford
ABSTRACT: This article compares and contrasts the pedagogies of both Estill Voice Training and Roy Hart voice work and discusses the possibilities for complementary vocal development offered by these approaches to voice training practices. With particular attention given to history and philosophy, this article proposes that the two models can provide, with differing emphases, a balance between technical skills and imaginative freedom, with the intention of laying the groundwork for access to the intangible aspects of vocal performance through the expression of the self with the voice. The article concludes that Estill Voice Training and Roy Hart voice work are distinct but complementary pedagogies and gestures toward the potential benefits of developing a multidisciplinary approach that incorporates aspects of these two pedagogies to provoke a vivid vocal development that can enable the capacity for healthy and freely expressive voices.